Development of Learning Tools for Character Value Education Subjects Based on Local Wisdom of Maluku Culture in the History Education Study Program of Unpati - Bety D.S Hetharion (International Journal of Education, Information Technology, and Others, 2021)
This study aims to develop textbooks to support efforts to strengthen history education study program students in understanding the competencies achieved in the Character Value Education course. This study used method development research consisting of two stages, namely the preliminary study stage and thestage formative evaluation. The results of the study provide meaning and urgency for character education, learning formats and integrating local culture in Maluku in character education learning. To provide understanding of how to act for students when facing life's phenomena and dilemmas correctly. Character ducation can develop cultural values ​​as an integrated cultural character teaching material in relation to the development of character education.